Diet and cancer - Divisi, D.; Di Tommaso, S.; Salvemini, et al., S. (Acta Biomedica Atenei Parmensis, 2006)
The aim of our study is to evaluate the relationship between diet and cancer development. It has been estimated that 30-40% of all kinds of cancer can be prevented with a healthy lifestyle and dietary measures. A low use of fibres, the intake of red meat and an imbalance of Omega-3 and Omega-6 fats may contribute to increase the risk of cancer. On the other hand, the assumption of lots of fruit and vegetables may lower the risk of cancer. Protective elements in a cancer-preventive diet include selenium, folic acid, vitamin B12, vitamin D, chlorophyll and antioxidants such as carotenoids (a-carotene, b-carotene, lycopene, lutein, cryptoxanthin). Ascorbic acid has limited benefits if taken orally, but it effective through intravenous injection. A supplementary use of oral digestive enzymes and probiotics is also an anticancer dietary measure. A diet drawn up according to the proposed guidelines could decrease the incidence of breast, colon-rectal, prostate and bronchogenic cancer.